(untitled) (Research, Society and Development, 2023)
To describe the collaborative competencies developed from the activities inducing interprofessional education at PET-Saúde / Interprofessionality in primary care in Pontal do Araguaia – MT. Methodology: This is a study with a quantitative approach, based on action developed during the execution of the PET-Saúde / Interprofessionality. For data collection, the Likert scale developed by the researchers and a questionnaire with sociodemographic questions were used. Students and professors from the courses in the health area of the Federal University of Mato Grosso, Campus Araguaia and also preceptors of the Municipal Health Department of Pontal do Araguaia participated. Results: Of the total of 56 participants in the PET Health, 53 (94.6%) participated in the study, 29 (54.7%) were students, 15 (28.3%) were preceptors and 9 (17%) were tutors. There was a predominance of young people aged 15-29 years (58.5%) and females (69.8%). All collaborative competencies were developed during the program. Team functioning, clarity of roles and collaborative leadership stand out with the highest percentages (above 77%) of agreement. The restrictive measures imposed by the pandemic scenario did not prevent, but influenced the outcome of competencies, interprofessional communication, user-centered care and conflict resolution, due to the impossibility of providing moments of exchange of ideas and experiences in person. Conclusion: The inducing activities promoted by interprofessional education and developed in primary care, even in atypical period and with the use of non-face-to-face activities, enabled the development of collaborative competencies.